100 UMP students receive laptop assistance from FGV Holdings Berhad Group - Mimi Rabita, Abdul Wahit (2023)
PEKAN, 15 February 2023 - A total of 100 Universiti Malaysia Pahang (UMP) students received laptop assistance from FGV Holdings Berhad Group in collaboration with Muslim Care Malaysia to fulfil their social responsibilities to the community.